QBO modulation of MJO teleconnections in the North Pacific: impact of preceding MJO phases - Min-Jee Kang; Hera Kim; Seok-Woo Son (npj Climate and Atmospheric Science, 2024)
Abstract This study examines the influence of the Quasi-Biennial Oscillation (QBO) on the Madden-Julian Oscillation (MJO) teleconnections in the North Pacific using ERA5 data. It is found that the Rossby wave trains induced by MJO phase 6–7 exhibit greater strength and robustness during the westerly QBO winter (WQBO) than during the easterly QBO winter (EQBO), although the MJO itself is weaker during the former. This counter-intuitive dependency of MJO teleconnections on the QBO is attributed to the preexisting MJO teleconnections prior to the MJO phase 6–7. The MJO phase 6–7 is more frequently preceded by stronger MJO phase 3–4 during the EQBO than during the WQBO. The preceding MJO phase 3–4 teleconnections, which have opposed signs to the MJO phase 6–7 teleconnections, result in a considerable attenuation of the MJO phase 6–7 teleconnections by destructive interference. This result is supported by linear model experiments. The subseasonal-to-seasonal prediction models also indicate improved prediction skills of MJO phase 6–7 teleconnections during the WQBO compared to the EQBO. These results suggest that enhanced MJO activities during the EQBO do not necessarily result in stronger and more robust MJO teleconnections in the North Pacific.